2018
DOI: 10.18203/issn.2454-5929.ijohns20183710
|View full text |Cite
|
Sign up to set email alerts
|

A rare cause for aphonia - Ortners syndrome

Abstract: <p>Rheumatic mitral stenosis is prevalent in the developing world and presents with a wide array of manifestations. Aphonia and hoarseness of voice secondary to recurrent laryngeal nerve paralysis (Ortner’s syndrome) is an uncommon manifestation of mitral stenosis. We present a case severe mitral stenosis with moderate to severe tricuspid valve regurgitation and severe pulmonary artery hypertension that was masquerading as aphonia and hoarseness of voice for eight months. Mitral valve replacement and tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Moreover, left atrial lesions due to mitral valve disease, presented in 20 patients (7.81%), and congenital heart defects presented in 14 patients (5.47%) (Yuan, 2014). There are several cardio-vocal syndrome cases is reported, Tammiraju et al and Ramasamy et al reported that hoarseness due to mitral stenosis (Tammiraju et al, 2018) (Ramasamy, Kale, Ramalingam, & Veerappa, 2018), and Chen et al in 2009 reported that hoarseness due to large aortic arch aneurysm (Chen, Lin, & Lu, 2009). There is no study nor literature mention the exact number of the incidence of Cardio-vocal syndrome in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, left atrial lesions due to mitral valve disease, presented in 20 patients (7.81%), and congenital heart defects presented in 14 patients (5.47%) (Yuan, 2014). There are several cardio-vocal syndrome cases is reported, Tammiraju et al and Ramasamy et al reported that hoarseness due to mitral stenosis (Tammiraju et al, 2018) (Ramasamy, Kale, Ramalingam, & Veerappa, 2018), and Chen et al in 2009 reported that hoarseness due to large aortic arch aneurysm (Chen, Lin, & Lu, 2009). There is no study nor literature mention the exact number of the incidence of Cardio-vocal syndrome in Indonesia.…”
Section: Introductionmentioning
confidence: 99%